Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
1)Solving the expression [tex]1-2(2x+1)=1-(x-1)[/tex] we get [tex]\mathbf{x=-\frac{1}{3}}[/tex]
2) solving the equation [tex]3.6x-6.1=5.9-2.4x[/tex] we get [tex]\mathbf{x=2}[/tex]
Step-by-step explanation:
We need to solve the expressions:
1) [tex]1-2(2x+1)=1-(x-1)\\[/tex]
Solving
[tex]1-2(2x+1)=1-(x-1)[/tex]
First solving the brackets
[tex]1-4x-2=1-x+1[/tex]
Simplifying
[tex]-1-4x=-x[/tex]
Adding 4x on both sides
[tex]-1-4x+4x=-x+4x\\-1=3x[/tex]
Switching the sides
[tex]3x=-1[/tex]
Divide both sides by 3
[tex]\frac{3x}{3}=-\frac{1}{3}\\x= -\frac{1}{3}[/tex]
So, Solving the expression [tex]1-2(2x+1)=1-(x-1)[/tex] we get [tex]\mathbf{x=-\frac{1}{3}}[/tex]
2) [tex]3.6x-6.1=5.9-2.4x[/tex]
Solving:
[tex]3.6x-6.1=5.9-2.4x[/tex]
Adding 6.1 on both sides
[tex]3.6x-6.1+6.1=5.9-2.4x+6.1\\3.6x=12-2.4x[/tex]
Adding 2.4x on both sides
[tex]3.6x+2.4x=12-2.4x+2.4x\\6x=12\\[/tex]
Divide both sides by 6
[tex]\frac{6x}{6}=\frac{12}{6}\\x=2[/tex]
So, solving the equation [tex]3.6x-6.1=5.9-2.4x[/tex] we get [tex]\mathbf{x=2}[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.